Implementasi Sistem Penjualan Online Pada PT. Prima Alkesindo Nusantara Jakarta - Angelina Hadriani Hadriyanto; Fathur Rozi; Rima Aulia (LPPM STMIK AL MUSLIM, 2024)
Prima Alkesindo Nusantara is a company engaged in the sale of medical devices. In carrying out current service activities, PT. Prima Alkesindo Nusantara is still centered on a specific location. This certainly makes it difficult for management to expand sales. The methods used to create this system are waterfall method with Xampp software tool with web, and Unified Modeling Language (UML). Up to the testing stage, which uses blackbox testing that is tested for consumers, admins and managers and PHP programming languages with supported MySQL databases. With this web-based information system can realize sales in conducting product transactions and save time in making reports. In addition, this web application not only aims to speed up and simplify the process, but can also have an impact on the neatness of the administrative system in the company. Keywords: Information Systems, Sales, UML, PHP and MySQL